The Strength Of Proof Of An Unregistered Marriage Agreement - Ratna Putrial Ayubahagiani; I Ketut Oka Setiawan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
The Nuptials treaty must be registered, in order to meet the publicity principle of the Nuptials treaty, so that third parties (outside the husband or wife) know and are subject to the rules in the Nuptials treaty that has been made by the couple. If not registered, then the Nuptials treaty is only binding / valid for the parties who make it, namely the husband and wife concerned. This is in accordance with Clauses 1313, 1314 and 1340 Civil Code. The nature or type of research conducted by the author is normative legal research. Normative legal research is legal research whose object is positive law as a system of norms. A system of norms refers to the principles, norms, and rules of legislation, court decisions, agreements, and doctrines (teachings). In normative legal research, the law being studied is described as “silent” law (law in the books). The authentic deed has infallible evidentiary force, as stated in Clause 1870 Civil Code. In terms of strength of proof, a Nuptials treaty made in the form of a notarial deed has perfect strength of proof regarding the content and existence of the treaty as Clause 1870 Civil Code, so that it can be used as valid evidence in court, that the parties have agreed to enter into the treaty and sign it before a notary. However, although the Nuptials treaty deed drawn up and signed before a Notary has a valid and strong evidentiary force between the parties who make it, the Nuptials treaty that is not registered does not have binding force against third parties because of the non-fulfillment of the principle of publicity, so that third parties can be considered unaware of the existence of the Nuptials treaty. In the event of a dispute involving a third party, the Nuptials treaty that is not registered does not have the force of proof against it.